2011
DOI: 10.1007/s00417-011-1700-2
|View full text |Cite
|
Sign up to set email alerts
|

Monocanalicular versus bicanalicular intubation in the treatment of congenital nasolacrimal duct obstruction

Abstract: BackgroundTo compare the success rate of monocanalicular intubation (MCI) compared with bicanalicular silicone intubation (BCI) in congenital nasolacrimal duct obstruction (CNLDO) in infants and toddlers.MethodsIn a prospective, nonrandomized, comparative study, MCI (n = 35 eyes) through the inferior canaliculus or BCI (n = 35 eyes) were performed under general anaesthesia in children aged 10 to 36 months with CNLDO. The tubes were removed 3–4 months after tube placement, and the children were followed up for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
36
1
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(45 citation statements)
references
References 11 publications
5
36
1
3
Order By: Relevance
“…This procedure is traditionally followed with canalicular stenting; both procedures are performed concurrently in the operating room, where surgical registration and preparation by the nurses are needed. [1][2][3][4][5] The patients always waited for several hours, or even days, until a nurse, the operating room, and the experienced ophthalmologist were simultaneously available. Experienced ophthalmologists at a large hospital often treat more than one patient at a time, and it is particularly illogical to always ask them to wait for the uncertain emergent surgical schedule during their rest time.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This procedure is traditionally followed with canalicular stenting; both procedures are performed concurrently in the operating room, where surgical registration and preparation by the nurses are needed. [1][2][3][4][5] The patients always waited for several hours, or even days, until a nurse, the operating room, and the experienced ophthalmologist were simultaneously available. Experienced ophthalmologists at a large hospital often treat more than one patient at a time, and it is particularly illogical to always ask them to wait for the uncertain emergent surgical schedule during their rest time.…”
Section: Resultsmentioning
confidence: 99%
“…[1][2][3][4] When evaluated for invasiveness, the nasal stenting is traditionally considered a more invasive technique because it is usually difficult to clamp the inserted antegrade suture crossing the inferior turbinate out of the inferior meatus, and it often needs to be assisted by an intranasal endoscope. 9,10 Sometimes, this process is time consuming.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[10][11][12] While bicanalicular intubation has been practiced since the 1970s, monocanalicular intubation did not start to become popular until the 1990s. [11] Both methods have their advantages and disadvantages.…”
Section: Discussionmentioning
confidence: 99%
“…[6,8,[10][11][12] In monocanalicular intubations, placement of the tube in the system can be sufficiently performed by entering only one punctum, where the tube is inserted from the upper and lower punctum in the ventricular intubation. [11,12] One of the most important advantages of the bicanalicular tube is that its surface is flatter [12][13][14] Monocanalicular tubes can cause abrasions or ulcers in the cornea, especially if they are placed in the upper canal and the collar side of the tube is larger. [14] Engel et al, [10] reported conjunctiva or corneal abrasion in 2% of 635 eyes where monocanalicular stapes were placed by upper canaliculus.…”
Section: Discussionmentioning
confidence: 99%